2009
DOI: 10.1590/s1983-32882009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of color spatial vision in chronic alcoholism measured by psychophysical methods

Abstract: We used psychophysical tests to evaluate spatial vision in 15 subjects with a clinical history of chronic alcoholism by measuring luminance contrast sensitivity and color discrimination. The subjects were initially subjected to clinical inquiry and ophthalmological exam. Subjects then performed psychophysical tests to measure spatial contrast thresholds using sine wave gratings of different spatial frequencies and contrasts and chromatic discrimination thresholds using the Mollon-Reffin test. For the analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
(72 reference statements)
1
3
0
4
Order By: Relevance
“…Our findings resemble those of Zhuang et al (2012) who observed a selective reduction of MC contrast sensitivity and PC contrast gain under acute alcohol consumption. They are also consistent with reports of impaired contrast sensitivity for both low and high spatial frequencies in SAUD (da Cruz et al, 2016; Oliveira Castro et al, 2009; Roquelaure et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings resemble those of Zhuang et al (2012) who observed a selective reduction of MC contrast sensitivity and PC contrast gain under acute alcohol consumption. They are also consistent with reports of impaired contrast sensitivity for both low and high spatial frequencies in SAUD (da Cruz et al, 2016; Oliveira Castro et al, 2009; Roquelaure et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…Já as pessoas com alteração hereditária, moderada ou severa, apresentam um padrão de deficiência caracterizado pela disposição bipolar dos gráficos e pela posição dos erros, os quais definem os eixos de confusão (Birch, 2001). Dentro desta proposta de avaliação, versões manuais e computadorizadas do teste são utilizadas nas pesquisas científicas para avaliar diversas patologias visuais, neurológicas e neurotóxicas (Castro et al, 2009;Pacheco-Cutillas, Sahraie & Edgar, 1999;Rodrigues et al, 2007;Ventura et al, 2003cVentura et al, , 2005. em inúmeros trabalhos em que foi medida a visão de cores em diferentes patologias (ver descrição detalhada adiante).…”
Section: O Ordenamento De Cores Pelo Teste De Farnsworth-munsell (Fm unclassified
“…Usando o CCT, Ventura e colaboradores (2003c) (Delahunt et al, 2004), parkinsonianos (Regan et al, 1998), sujeitos expostos ao consumo de álcool (Castro et al, 2009), usuários de cloroquina (Ventura et al, 2003c), neuropatia óptica hereditária de Leber ( Ventura et al, 2005( Ventura et al, , 2007a, pacientes com esclerose múltipla (Moura et al, 2008), com a distrofia muscular de Duchenne , intoxicados por mercúrio (Canto-Pereira et al, 2005;Feitosa-Santana et al, 2008;Rodrigues et al, 2007;Ventura et al, 2005). Também tem sido utilizado em pesquisas em ciência básica, como a avaliação da ausência de somação binocular, olho dominante e efeito da aprendizagem na discriminação de cores (Costa et al, 2006), aparência de cores para dicromatas (Brettel, Viénot, & Mollon, 1997), variações na mistura e discriminação de cores entre tricromatas e deuteranômalos, além de inspirar a criação de sistemas que usam o mesmo tipo de disposição do estímulo em mosaico para o estudo da discriminação do sistema visual humano (Figura 2) (Knoblauch, Vital-Durand, & Barbur, 2001;Rodrigues et al, 2007).…”
Section: O Ordenamento De Cores Pelo Teste De Farnsworth-munsell (Fm unclassified
See 1 more Smart Citation
“…O teste desenvolvido pelo grupo de Mollon, comercialmente conhecido como Cambridge Colour Test (CCT), mostra grande vantagem, pois possibilita a variação dinâmica e adaptativa da diferença cromática entre o alvo e o fundo ao longo das diferentes direções no espaço de cor (Regan, Refin, & Mollon,1994 (Delahunt et al, 2004), parkinsonianos (Regan et al, 1998), sujeitos expostos ao consumo de álcool (Castro et al, 2009), usuários de cloroquina (Ventura et al, 2002b), neuropatia óptica hereditária de Leber (Ventura et al, 2005, pacientes com esclerose múltipla (Moura et al, 2008), com a distrofia muscular de Duchenne , intoxicados por mercúrio (Canto-Pereira et al, 2005;Feitosa-Santana et al, 2008;Rodrigues et al, 2007;Ventura et al, 2005). Também tem sido utilizado em pesquisas em ciência básica, como a avaliação da ausência de somação binocular, olho dominante e efeito da aprendizagem na discriminação de cores (Costa et al, 2006).…”
Section: Test -Cct (Versão Original E Suas Novas Versões)unclassified